Hypolipidemia: a study evaluating magnitude and underlying etiologies of the entity - Mathur, Navgeet; Mehta, Amit; Mathur, Medha (International Journal of Advances in Medicine, 2021)
Background: Hyperlipidemia is a common and well-known entity as it is one of the risk factors of various noncommunicable diseases. Hypolipidemia is an entity which is very less known among health care givers. Currently available data about this entity is insufficient and nonconclusive. Methods: This study was a prospective observational study. Lipid profile reports at the central lab of the institute was observed and among them hypolipidemia reports and related patients were identified. Patients were further evaluated and classified into 10 etiological categories. Results: Total 450 lipid profile reports were observed out of which 36 (8%) reports had hypolipidemia. Most patients had hypolipidemia were having chronic illness (41.7%) or critical illness (33.3%) followed by malnutrition (11.1%), idiopathic etiology (11.1%), moderate to severe anemia (8.3%), chronic liver disease (8.3%), cancer (5.5%), statin use for more than 3 months (2.8%), malabsorption (2.8%), hyperthyroidism (0%). Conclusions: Awareness about hypolipidemia among health care givers is needed to look out for underline diseases with consequences and to have active participation to unsolved the mystery of this entity. Overuse of antihyperlipidemic drugs should be avoided. This study highlighted causes and consequences of hypolipidemia.